Praktik-Praktik Manajemen Keragaman di Tempat Kerja - Umbu Djadji, Osfred (Fakultas Ekonomi Universitas Samudra, 2023)
The research aims to analyze the factors that lead to diversity, the strategies in managing diversity, the practices in managing diversity, the impacts and constraints in managing diversity in organization. The research method uses a literature study that collects several previous studies to answer the practices of managing diversity in the workplace. The findings of the research demonstrate that the diversity management practices are still suboptimal and the discriminatory treatment still occurs which is marked by the triggers for diversity, the strategies in managing the diversity, and the challenges that employees face in the workplace. According to the research published in prior journals, the management restrictions are characterized by an imbalance in the number of employees, a lack of respect and support from colleagues, complaints and protests against the leadership, and a refusal to get along with colleagues.